Midnight on the Mississippi - Ellis, Mary, 1951- (Eugen, Oregon; Harvest House Publishers, 2015)
"New Orleans--Hunter Galen, a stock and securities broker, suspects his business partner, James Nowak, may be involved in embezzling their clients' money, but he's reluctant to jeopardize their friendship based on suspicion alone. After James turns up dead, Hunter realizes his unwillingness to confront a problem may have cost James his life. Nicki Price, a newly minted PI, intends to solve the stockbroker's murder, recover the missing millions from the client accounts, and establish herself in the career she adores. As she ferrets out fraud and deception at Galen Investments, Hunter's fiancee, Ashley Menard, rubs Nicki the wrong way. Nicki doesn't trust the ostentatious woman with an agenda longer than the Mississippi River. Ashley seems to be hiding something, but is Nicki's growing attraction to Hunter--a suspected murderer--her true reason for disliking Ashley? As they encounter sophisticated shell games, blackmail, and murder, Nicki and Hunter's only option is to turn to God as they search for answers, elude lethal danger, and perhaps discover love along the way."--Provided by publisher
Keywords: Women private investigators -- Louisiana -- New Orleans -- Fiction; Murder -- Investigation -- Fiction; Louisiana -- New Orleans; Christian fiction; Romantic suspense fiction; Fiction